Demographic structure and genetic diversity of the endangered Bísaro pig: Evolution and current status - Paixão, Gustavo; Esteves, Alexandra; Payan-Carreira, Rita; Carolino, Nuno (Czech Journal of Animal Science, 2018)
Bísaro pig, a local endangered swine breed, has gained popularity in the recent years. A complete pedigree was used to evaluate the population structure and investigate the current breed's genetic variability in two reference populations (AlivePop and AliveBpop). Since the breed's foundation, the number of registered animals, producers, and farrowing records has increased. The mean progeny size for sires was 116.17 ± 210.81, and 3.24% of the breeding boars originated 26.54% of all registered births showing a marked unbalanced use of certain sires. The mean calculated equivalent generations was 4.54, and 98.1% of all the animals had known parents, indicating a good degree of pedigree completion and depth. Approximately half of the individuals were inbred, with average inbreeding values of 10.41, 9.02, and 8.58% for the whole and reference populations, respectively. Considering both reference populations, a low effective founder/ancestor ratio was obtained (1.12), showing a well-balanced founder/ancestor contribution, and subsequent genetic transfer. However, the effective founder/founder ratio was particularly low (0.06 and 0.12) compared with other native breeds. The founder genome/effective founder ratios were 0.37 and 0.41 for AlivePop and AliveBpop. Contrarily to the whole population, the random genetic drift weighted significantly more than the drift due to unequal founder contribution in the reference populations. The effective population size based on the increase in coancestry ranged from 62.39 and 54.66, and 16.74 and 24.84 based on the increase of individual inbreeding, for the whole and reference populations. The genetic conservation index steadily grew over the years with a mean value of 6.53 for the whole pedigree. Genetic variability losses and diffuse structuring might have occurred in the Bísaro population. Notwithstanding, the recent genetic variability indicators seem positive, yet supported by an open herdbook policy. These characteristics must be taken into account to define future mating policies and selection programs.
Keywords: conservation; genetic variation; inbreeding; pedigree analysis; swine